EFFECTIVENESS OF SHOULDER ROM EXERCISES IN POST BREAST CANCER SURGERY: CASE REPORT - Firnadia Septika Rahajeng; Arif Pristianto; Nilam Nur Hamidah (CV. Fahr Publishing, 2024)
This study evaluated the effectiveness of Range of Motion (ROM) exercises in post-breast cancer surgery patients who experienced shoulder stiffness. This study used a case report method, which was carried out on a 33-year-old female patient with a diagnosis of shoulder stiffness after breast cancer surgery. Measurements were made using various parameters, namely pain level using the Numerical Rating Scale (NRS), muscle strength using Manual Muscle Testing (MMT), and shoulder functional ability using the Shoulder Pain and Disability Index (SPADI). The physiotherapy interventions provided include active and passive ROM exercises, as well as hold-relax techniques with variations in flexion extension, abduction-adduction, and internal-external rotation with a dose of 8 repetitions in 2 sets per therapy session. The results showed a significant reduction in pain, where movement pain decreased from NRS 5 to NRS 1, as well as an increase in muscle strength from level 3 to level 5. Joint range of motion (ROM) increased, with shoulder flexion from 90° to 170°, abduction from 75° to 170°, and external rotation from 40° to 90°. In addition, the SPADI score decreased from 39.30% to 14.00%, indicating an increase in shoulder functional ability. This study concludes that active and passive ROM exercises have proven to be effective in increasing joint flexibility, reducing pain, increasing muscle strength, and improving shoulder functional ability in post-breast cancer surgery patients. This exercise can be a recommended physiotherapy intervention in the rehabilitation of patients with similar conditions.